Assessment of the Potential Risk of Rock-Climbing for Cliff Plant Species and Natural Protected Areas of Spain - deCastro-Arrazola, Indradatta; March-Salas, Martí; Lorite, Juan (Frontiers in Ecology and Evolution, 2021)
In recent years, popularity of rock-climbing has grown tremendously, setting an increasing pressure on cliff habitats. Climbing may be particularly harmful in the Mediterranean biome due to its appropriate environmental conditions for climbing. A few studies have identified an effect of climbing on plant diversity at small-scale. However, no studies exist assessing the potential risk of rock-climbing at a broad-scale. Here, we aim to identify priority locations and cliff plant species of Spain to focus future study efforts. Spain was selected because it is a plant biodiversity hotspot, with a great diversity of endemic and endangered species, and one of the most popular destinations for climbers. We use a geographic information system-based approach to model spatial concurrence among Spanish climbing areas (and their climbing intensity), natural protected areas (NPAs) and distribution of threatened cliff plants (and their IUCN threat category). We found that 53.5% climbing areas in Spain are located within a NPA, most of them falling into NPAs of medium protection level. We mapped 151 threatened cliff plants, identifying four medium priority locations and eight priority species in which future research efforts should be focused. For the first time at a national scale, this study identifies areas in which climbing represents a potential threat for cliff habitats and for threatened plants. These findings contribute to designing field studies on the effects of rock-climbing on Mediterranean cliffs, laying the groundwork for a sustainable, yet challenging, balance between the protection of these unique habitats and rock-climbing.